Bankruptcies, bailouts, and some political economy of corporate reorganization. Issue 5 (19th February 2018) - DELLISANTI, DYLAN; WAGNER, RICHARD E.
Abstract: Bankruptcy has long been the standard approach to reorganizing failing corporate entities. In recent years, bailout, whereby a governmental entity takes charge of the reorganization, has appeared as an alternative. At the enterprise level, there is a Coase-like invariance proposition at work in which a failing concern is replaced by a going concern under either process. Significant differences arise once we move beyond the point of reorganization. The choice between bankruptcy and bailout is fundamentally a choice between alternative arrangements for corporate governance, and not about transforming failing concerns into going concerns because this will happen under either arrangement. We argue that political entanglement in corporate restructuring will tend to preclude the entrepreneurial discovery process. We recount the recent American auto and financial industry bailouts, highlighting how each episode was guided by political considerations, which served to distract the restructuring process from discovering those opportunities that market-based restructuring would have discovered.